Visualizing the maritime connectivity of African countries - (:unkn) unknown (My University, 2022)
Containerization is still on-going in Africa. In the last decades, a number of new port and terminal projects have emerged in parallel with the reorganization of services by shipping lines. To support the analysis of the maritime connectivity of African countries, this paper proposes a visualization of the Liner Shipping Bilateral Connectivity Indicator (LSBCI).
Keywords: African Research